Ghost in the garden - Herman, Gail 1959- (New York : Scholastic, 2000)
Scooby-Doo and the gang come to the rescue when Farmer Fran tells them a ghost has taken all of the lettuce and carrots from her garden.
H
480
Keywords: Dogs -- Fiction; Ghosts -- Fiction